Orthosomnia: Is it the New Sleep State Misperception Experience? - Sexton-Radek, Kathy (Archives of Case Reports, 2026)
A case study of a seventy-two year old female referred to the Insomnia clinic for a longstanding sleep disturbance is presented. The incidence of sleep disturbance in the older adult population is common. A typical onset following retirement from the structure of a work schedule and/or transition away from child/family member in-home care. A common co-existing issue with sleep disturbance in this population is the increased incidence of medical conditions and use of prescribed medications. A clinical history of the patient’s sleep and general health was followed by the completion of standard measures of the Pittsburgh Sleep Quality Index and the Epworth Sleepiness Scale. The patient was provided with an explanation of CBTi and requested to begin tracking her sleep using a standard sleep log form. In addition, per the patient’s request, data was included from wearables that she was using. Wearables are commonplace today, but the link to empirical utility and impact on the patient is at present understudied. A summary of the interview and standard scales findings is presented, as well as weeks one and two of the baseline sleep logging. The focus of this article is the patient’s response to the wearable data and her experience reporting her sleep. The patient continued to CBTi treatment following the assessment, and the baseline was reported to her. For a description and details about CBTi, consult Sexton-Radek and Graci.